Optimization of Injection Moulding Parameters for Constructing Motorcycle Footstep Cover Using an Environmentally friendly Composite - Rifai, Muhammad Fajar; Widiastuti*, Indah; Saputra, Taufik Wisnu (Graduate School of Universitas Syiah Kuala, 2023)
Agra-forestry waste and recycled polypropylene have been combined to create sustainable composite materials for use in automotive applications in response to increased environmental concern over the depletion of petroleum-based resources. In this study, an injection molded motorcycle footstep cover was manufactured from recycled polypropylene (rPP) composite reinforced with ironwood powder. It aims to optimize the manufacturing process parameters of barrel temperature, mould temperature, and holding time in minimizing shrinkage and maximizing product weight. This current research employed the Taguchi L4 orthogonal array experimental design followed by the multi-objective grey relation analysis (GRA). In this study, the composite material consisted of 30% ironwood powder, 65% r-PP, and 5% coupling agent. The specimens were processed using injection molding with two different levels for each parameter of barrel temperature, moulding temperature, and holding time. The injection moulded products were then tested for shrinkage and product weight. The results showed that moulding temperature was the most influential parameter in getting a minimum shrinkage percentage, contributing 60.89%. Meanwhile, holding time contributes the most to achieving a maximum product weight (90.65%). After conducting a grey relation analysis and a confirmation test, the optimal parameters for shrinkage minimization and product weight maximization of motorcycle footstep cover are 210 of barrel temperature, 45 of moulding temperature, and 5 seconds of holding time. This research highlights the prospective applications of recycled polypropylene composite reinforced with ironwood powder for application as automotive parts.